Pengembangan Ekonomi Digital di Provinsi Gorontalo: Analisis Potensi dan Tantangan - s.r Sahrain, Asral Kelvin (Madani: Jurnal Pengabdian Ilmiah, 2024)
This study aims to analyze the potential and challenges of developing a digital economy in Gorontalo Province, particularly in the tourism sector. Using a qualitative method through interviews and observations of tourism SMEs and communities, this research found that Gorontalo has significant potential in digital economy development, with 70% of tourism SMEs already utilizing social media for promotion. However, several challenges were identified, including limited digital infrastructure with internet penetration below 40% in rural areas, low digital literacy with 65% of SMEs struggling to operate digital platforms, and security concerns with 72% of respondents expressing worries about data security and fraud risks in digital transactions. The results suggest the need for collaborative efforts from government, community, and business actors in strengthening digital infrastructure, enhancing digital literacy, and developing reliable digital security systems to maximize the potential of the digital economy in Gorontalo.